Peningkatan Pengetahuan SDM Melalui Pendampingan Pengembangan Website Sekolah di Daerah Tertinggal - Rizal Bakri; Hartoto Hartoto; Nurlaely Razak (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. The Partners of the Community Stimulus Partnership Program (PKMS) is the Regional Office of Education and Culture, Bangkala District, Jeneponto Regency, which involves eight State Junior High Schools. The problems are (1) lack of knowledge about the benefits of Information Technology related to websites, (2) there is no official school website that has a .sch.id domain, (3) lack of skills in developing School websites, and (4) lack of knowledge on promotion Schools through digital media management on the website. This activity aims to develop official websites for eight State Junior High Schools that have high economic value to promote the excellence of the School. The method used is the hybrid learning method, namely: lectures, demonstrations, discussions, questions and answers, and companion partners, either directly or virtually. The results achieved are (1) partners know the benefits of Information Technology, especially School websites, (2) partners can develop and manage school websites, (3) the availability of eight school websites that can be accessed online, and (4) capable partners create attractive content and digital media as materials to raise the profile of the School.